Rancang Bangun Mesin Pencetak dan Pemotong Briket dengan Sistem Elektro Pneumatik untuk UMKM - Elvis Adril; Menhendry Menhendry; Daddy Budiman; Maheka Restu Araliz4; Ayu Pitri Yeni (Politeknik Negeri Padang, 2024)
Briquettes are an alternative fuel based on biomass waste which is available in very abundant quantities, one of which is coconut shell waste. The briquette processing process is generally still done manually. Therefore, a machine with automatic control using an electro-pneumatic system was built with the aim of avoiding product failure due to human error and this machine will be useful for UMKM. The working principle of this machine is to use a screw press for printing and electro-pneumatics for the cutting step. From the results of the design for this briquette printing and cutting machine, the briquettes produced have a diameter of 52 mm. This briquette printing and cutting machine uses a motor power of 0.75 HP and a rotation of 3500 rpm. The printer screw rotation speed is 28 rpm which is produced by using 2 inch and 5 inch pulleys and using a WPA 40 reducer gearbox with a ratio of 1:50. Meanwhile, for cutting using a sensor to detect the length of the briquette, it will then be cut by a plate connected directly to the pneumatic cylinder